Performance evaluation of a rectifier column using gamma column scanning - Aquino Denis D.; Mallillin Janice P.; Sulit Ramoncito F.; Hila Frederick C.; Nuñez Ivy Angelica A.; Bulos Adelina D. M. (Nukleonika, 2017)
Rectifier columns are considered to be a critical component in petroleum refineries and petrochemical processing installations as they are able to affect the overall performance of these facilities. It is deemed necessary to monitor the operational conditions of such vessels to optimize processes and prevent anomalies which could pose undesired consequences on product quality that might lead to huge financial losses. A rectifier column was subjected to gamma scanning using a 10-mCi Co-60 source and a 2-inch-long detector in tandem. Several scans were performed to gather information on the operating conditions of the column under different sets of operating parameters. The scan profiles revealed unexpected decreases in the radiation intensity at vapour levels between trays 2 and 3, and between trays 4 and 5. Flooding also occurred during several scans which could be attributed to parametric settings.